Interactive Role of Consumer Discrimination and Branding against Counterfeiting: A Study of Multinational Managers’ Perception of Global Brands in China - Sonmez, Mahmut; Yang, Deli 1964-; Fryxell, Gerald (2013)
Prior research has examined consumer intentions to purchase fakes, branding strategies and anti-counterfeiting actions, but little attention seems to have been paid to the role of consumers’ ability to discern fakes and branding strategies against counterfeiting. This article, thus, based on a study of 128 multinational managers’ experience in China, examines these inter-relationships. As a result, we address how knowledgeable and experienced managers in branding, consumer consumption and anti-counterfeiting effort perceive consumers’ ability to discriminate fakes from originals interacts with branding strategies, and how such relationship influences the effectiveness of anti-counterfeiting effort. Our findings suggest that consumer discrimination itself has no significant effect on anti-counterfeiting success. However, it significantly interacts with branding strategies to predict a means to mitigate brand damage. That is, consumers’ ability to discriminate fakes from originals appears to undermine efforts to mitigate brand damage from counterfeiting, at least in China when branding is based on improving product features or advertising and promotion. However, if branding emphasises after sales service, consumers’ ability to discriminate was found to enhance firms’ ability to limit counterfeiting damage to brands. Such interactions, however, did not help stop counterfeiting, except that branding based on reliability appears to have such a positive effect.
Keywords: Global brand; Counterfeiting; Consumer discrimination; Managerial perception; Branding; Anti-counterfeiting success